What constitutes victims of toxicity - identifying drivers of toxic victimhood in multiplayer online battle arena games - Kordyaka, Bastian; Laato, Samuli; Weber, Sebastian; Niehaves, Bjoern (Frontiers in Psychology, 2023)
Toxic behavior (also known as toxicity) in online gaming communities, such as League of Legends, is a pervasive and detrimental problem arising from factors such as frustrating in-game experiences of players and online disinhibition. Past work has extensively focused on the perpetrators of toxicity, and how to curb players toxic tendencies or the consequences of their actions. In this study, we look at the other side of the coin, and focus on the role of victims of toxicity. Building on previous work related to toxicity, and through the lenses of online disinhibition, social cognitive theory, and the theory of planned behavior, we formulate hypotheses to explore what causes players to experience victimhood at the population level. For this, we collected data from a global sample of League of Legends players and Defense of the Ancients 2 (n=313) to test the hypotheses. The results revealed that scoring high on self-efficacy, and benign and toxic disinhibition, were the most relevant antecedents for the experience of being a victim of toxicity. The findings of this study provide insight into the prevalence and impact of toxic behavior in the gaming community, as well as strategies for dealing with such behaviors and creating a more positive and inclusive gaming environment.